The Effect of Using Digital Sequence Pictures on Students' Ability in Writing Explanation Text - Meisyani Gustri Fadila; Fitrawati Fitrawati (Universitas Negeri Padang, 2022)
The purpose of this research was to find out the effect of using digital sequence pictures on students’ ability in writing an explanation text. This research design was quasi-experimental research and had two classes which were the control class and the experiment class. The population of this research was the second-year students at SMA N 1 Lengayang and the sample was decided by using cluster random sampling which was getting two classes. XI.IPA 1 was the experiment class and XI.IPA 2 was the control class. The writing test was administrated as the instrument of this research which was writing an explanation text. After collecting the data, the data were analyzed by the paired sample t-test. The result of paired sample t-test in the research stated that the value of sign 2-tailed is 0.000 which means that the value of the sign. 2-tailed lower than 0.05 so that the alternative hypothesis or the first hypothesis was accepted. In conclusion, the results of the data showed that there was a statistically significant improvement in the explanation text which is written by the students after they were taught through the digital sequence pictures. The findings suggest that the digital sequence pictures enable students to improve their ability in writing an explanation text.